ANALISIS KUALITATIF ZAT BIOAKTIF PADA EKSTRAK DAUN ALPUKAT (Persea americana Mill) DAN UJI PRAKLINIS DALAM MENURUNKAN KADAR GLUKOSA DARAH PADA MENCIT (Mus musculus) - Putri, Eska Perdanawati Kahar; Hamzah, Baharuddin; Rahman, Nurdin (Universitas Tadulako, 2013)
Diabetes is the oldest disease in the world, the death rate cause by diabetes mellitus is increasing. This study aims to know bioactive substances of avocado leaf and effective concentrate in decreasing the level of mice blood glucose. The study apply experimetal method to analyze bioactive substance in avocado leaf extract qualitatively. Whereas the preclinical testing use random group design. This study used 15 male mice as test animal which are induced with etilen diamin tetra asetat (EDTA). The mice are divided into 5 groups (n=5) randomly with different treatment. Treatment I, II, III are given avocado leaf extarct each with concentrate of 10%, 20% and 40%, treatment IV is given suspension of glibenklamid as a positive control (+) and treatment V is given 1% suspension of sodium carboxymethil cellulose (Na-CMC) as a negative control (-). Data obtained is analysed by using statistical analysis of varians (ANOVA) wich is continued with Duncan test. The research result shows that advocado leaf extract positively contains compounds of alkaloid, flavonoid, saponin, tanin and steroid. Praclinic test shows that advocado leaf extract proven can lower the level of mice glucose and relatively the most effective concentrate is 10%.